(untitled) (Sustainability in Debate, 2015)
Mining is considered one of the basic sectors of Brazil’s economy. It provides basic raw material for industry, and several products - from the simplest to the most complex ”“ have a mineral origin. The most significant products mined in Brazil, by their volume, are sand and crushed stone. Sand extraction activities are of great importance for social development, but equally accountable for their negative environmental impacts, some of which are irreversible. Due to the activity location’s rigidity, sand mining companies are forced to focus where there is mineral occurrence. Sand locations are constantly placed near the bottom of valleys and rivers, often coinciding with riparian forests - usually permanently protected areas. In this context, this article’s objective is to demonstrate, through a dialectical approach and literature review, the possibility of conciliating the exploitaton of sand in permanently protected areas. The article analyses the implications of Law 12.651/12 (New Forest Law), It will also exanine the activity’s socioeconomic and environmental impact, which has to be taken into account to achieve the environmental function of property.